Toward functioning and usable brain-computer interfaces (BCIs): A literature review. - Pasqualotto, Emanuele; Federici, Stefano; Belardinelli, Marta Olivetti (Disability & Rehabilitation: Assistive Technology, 2012)
Purpose: The aim of this paper is to provide an exhaustive review of the literature about brain--computer interfaces (BCIs) that could be used with these paralysed patients. The electroencephalography (EEG) is the best candidate for the continuous use in the environment of patients' houses, due to its portability and ease of use. For this reason, the present paper will focus on this kind of BCI. Moreover, it is our aim to focus more on the patients, regarding their active role in the modulation of the brain activity. This leads to a differentiation between studies that use an active regulation and studies that use a non-active regulation. Method: Relevant articles in the BCIs field were selected using MEDLINE and PsycINFO. Results: Research through data banks produced 980 results, which were reduced to 127 after exclusion criteria selection. These references were divided in four categories, based on the use of active or non-active regulation, and on the event related potential used. Conclusions: In most of the examined works, the focus was on the development of systems and algorithms able to recognise and classify brain events. Although this kind of research is fundamental, a user-centred point of view was rarely adopted.